TRANSFER OF AUTHORITY OF THE INDONESIAN MEDICAL COUNCIL TO ISSUE REGISTRATION CERTIFICATES FOR MEDICAL PERSONNEL - Handayani, Syofini; Noor, M. Tauchid; Nugraheni, Ninis (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
This research aims to analyse the basic legal ratio of the authority of the Indonesian Medical Council in issuing Registration Certificates for medical personnel and to analyze the legal consequences of issuing Registration Certificates for medical personnel by the Indonesian Medical Council after the issuance of Law Number 17 of 2023 concerning Health. The research approach used was normative juridical research. The legal materials used were primary and secondary legal materials. The technique for collecting legal materials in this research was by conducting a literature study. The research results showed that after the issuance of Law 17/2023, the central government through the Minister of Health is simplifying the practice requirements for medical personnel by introducing lifetime STR and SIP with the SKP system which is assessed directly by the Minister of Health and Regional Government. The legal consequences are not only a shift in norms, but also the formation of a new council with the latest structure, the SKP requirements shifted from the issuance of STR to SIP, and also the emergence of SKP management authority by the Regional Government c.q. Head of the Regency/City Health Service or Head of the Regency/City Regional Investment and One-Stop Integrated Services